Standardizing the Ignition Delay Time Measurements of Rapid Compression Machine: An Inverse Application of the Livengood–Wu Integral Method - Zhonghao Zhao; Yingtao Wu (Energies)
The rapid compression machine measures ignition delay time at high pressures and low to intermediate temperatures. However, unavoidable facility effects, such as compression and heat loss, shift the measurements away from ideal (adiabatic and constant volume) values to varying extents. Consequently, the ignition delay times measured by different facilities can be in large deviations, especially for fuel mixtures without negative temperature coefficient behavior. To address this issue, this work proposes a standardization algorithm that correlates the measurements to the ideal ignition delay times. The algorithm applies the Livengood–Wu integral method inversely and adopts a Bayesian approach to optimize the correlation parameters. The ignition delay times of an ethanol mixture under distinct facility effects were further used to test the performance of this algorithm. The results show that the dispersed ignition delay times can be effectively standardized within 20%, facilitating the direct comparison of measurements from different facilities. By setting a proper residual target of the algorithm, reasonable standardization accuracy can be achieved. This method enables a significantly easier interpretation of the rapid compression machine experimental data and can be broadly applied to any fuel mixtures exhibiting single-stage ignition characteristics.